PCOS and pregnancy: a review of available therapies to improve the outcome of pregnancy in women with polycystic ovary syndrome. Issue 2 (4th March 2018) - Artini, Paolo Giovanni; Obino, Maria Elena Rosa; Sergiampietri, Claudia; Pinelli, Sara; Papini, Francesca; Casarosa, Elena; Cela, Vito
ABSTRACT: Introduction : Polycystic ovary syndrome (PCOS) is a common cause of female infertility affecting multiple aspects of a women's health. Areas covered : The aim of this review is to summarize the existing evidence on the treatment of PCOS patients and to examine the actual available therapies to overcome the problem of infertility and improve the outcome of pregnancy. We analyse different treatment strategies such as lifestyle modification, bariatric surgery, insulin sensitizing agents, inositol, clomiphene citrate (CC), aromatase inhibitors, gonadotrophins, laparoscopic ovarian drilling, and assisted reproductive techniques (ART). Expert commentary : Lifestyle modification is the best initial management for obese PCOS patients seeking pregnancy and insulin sensitizing agents seem to have an important role in treating insulin resistance. Up to now, CC maintains a central role in the induction of ovulation and it has been confirmed as the first-line treatment; the use of gonadotrophins is considered the second-line in CC resistant patients; laparoscopic ovarian drilling is an alternative to gonadotrophins in patients who need laparoscopy for another reason. However, in anovulatory patients, ART represents the only possible alternative to obtain pregnancy. Larger and well-designed studies are needed to clarify the best way to improve the outcome of pregnancy in PCOS women.